Penerapan Metode Pembelajaran Bervariatif Untuk Meningkatkan Hasil Belajar - Haholongan Simanjuntak; Rosmala Rosmala (JURNAL MATHEMATIC PAEDAGOGIC, 2023)
The purpose of this study was to find out how the application of various learning methods to the learning outcomes of fifth grade students at SD Negeri 15 Toboali on the area of flat shapes. This research was conducted on fifth grade students of SD Negeri 15 Toboali. After learning that applied various learning methods to the material "Area of Flat Shape" in Mathematics learning, the following results were obtained: (1) from the aspect of the learning process, students were actively involved in learning activities from Cycle I to Cycle III; (2) there was an increase in students' academic ability, namely students' mastery of the concept of learning material, starting from cycle I to cycle III the average score of students increased so that it reached 82.69; and (3) in terms of student activity, the score obtained in Cycle III was 83.65 and in terms of student cooperation, a score of 82.69 was obtained in Cycle III. Based on the values, activeness, and cooperative attitudes obtained by students, it can be concluded that the application of various learning methods can improve student learning outcomes and be used in learning at school, especially learning "Area of Flat Shape" in Mathematics.